Analisis Swot Pada Umkm "Cemilan Nusantara" Dalam Pengembangan Produk Keripik Singkong Premium Di Era Digitalisasi Eko Budi Prastyo - Eko Budi Prastyo (Jurnal Ekonomi dan Bisnis Digital, 2025)
The "Cemilan Nusantara" MSME produces premium cassava chips made from organic cassava with a variety of modern flavors. Amidst the development of digitalization and changes in consumer behavior, a SWOT analysis is necessary to identify the strengths, weaknesses, opportunities, and threats faced in developing its business. This study uses a descriptive method with a SWOT approach to design a relevant business strategy. The results indicate that "Cemilan Nusantara" is in Quadrant I (aggressive strategy), thus needing to maximize internal strengths and external opportunities to strengthen its competitiveness in the local and digital markets.